Delving into the Implementation of Malaysia's Pioneer Paddy Crop Takaful Scheme: Issues and Insights - Syahnaz Sulaiman (www.amertainstitute.com, 2024)
The agricultural sector is a cornerstone of Malaysia's economy and food security, yet it faces persistent risks, including climate change, pest infestations, and natural disasters. In response, paddy crop takaful schemes have been proposed as a Shariah-compliant financial tool to mitigate these risks and protect vulnerable farmers. However, despite its potential, these schemes encounter few implementation challenges. This study explores some issues surrounding its implementation based on the observation of a number of key institutions namely takaful operators, zakat and waqf institutions as well as agriculture agencies in promoting the participation of paddy farmers in the takaful schemes. The research adopts a qualitative approach, combining document analysis with semi-structured interviews. Data were gathered from takaful operators, zakat and waqf institutions, and officers from agricultural agencies within the year of 2024. The findings reveal several recurring challenges based on involvement of few agencies in the scheme. This study underscores the need for targeted awareness campaigns, policy support, and innovative integration of Islamic social finance mechanisms that has the potential to enhance paddy crop takaful. By leveraging insights from institutional perspectives, the findings contribute to designing more effective and inclusive paddy crop takaful schemes, enhancing resilience within Malaysia’s agricultural sector.